PERFORMANCE HOMEWORK FOR BASKETBALL PLAYERS - Jukic, Igor (Sport- és Egészségtudományi füzetek, 2026)
Igor Jukic’s presentation focus on the performance homework for basketball players, but from the perspective of the players needs, which is sometimes different from the way of thinking and the perspective of the coaches. Many issues are related to players’ private lifes, and those who will have control, or more influence on time, what players spend without the coaching staff, will take advantage. Jukic talked on behalf of the Performance Advisory Board of Euroleague Players Associations. They think it is not easy to change their mindset and start to consider first from the players’ point of view and start to speak their language. This is very important because sometimes academic language is so far from players’ way of understanding basic topics and basic issues they have in everyday life.